Building Established Suburbs Upwards: Case Studies of New Development Projects in Long Island, NY. - Rebecchi, Jeanette. (2017)
Abstract: This thesis focuses on the barriers higher density suburban infill projects face during the municipal review and permitting phase, and why some projects are ultimately approved and others are not by the local governing body. Relevant literature commonly cites zoning and regulatory issues, lack of leadership by local officials, poor outreach and communication amongst stakeholders, and community opposition as significant barriers. Two Long Island, New York case studies are used in this thesis, AvalonBay in Huntington Station and the New Village in Patchogue. They examine what development barriers were in place within the community, and why the New Village was granted an approval by the local Board and AvalonBay was not. What was found was that while both projects did comparable levels of community outreach, other important factors such as historic and contemporary events, social media, municipal procedure, government structure and leadership, and the design of the project appeared to impact success or failure.; Thesis (M.A.)--Tufts University, 2011.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Justin Hollander.; Committee: Peg Barringer.; Keyword: Urban planning.